Occurrence of Gaibulus schubarti Roewer 1973 (Opiliones: Stygnidae) in treefall gaps of Atlantic forest - Andrade, Alessandra Rodrigues Santos de; Peres, Marcelo César Lima; Benati, Kátia Regina; Dias, Marcelo Alves (SITIENTIBUS série Ciências Biológicas, 2009)
This paper aimed increase the knowledge of the Northeast Brazilian opiliofauna and compare the environmental data and Gaibulus schubarti abundance between two forest habitats: treefall gaps and adjacent forest, and also, verify if the litter cover and thickness would influence their abundance. In the Pituaçu Metropolitan Park (425 ha), Atlantic Forest’s fragment, 12 sites (six gaps and six forest). Across 12 months, micro-habitats and micro-climate variables were collected monthly on the 12 sites, throw 144 litter samples (50x50cm). MRPP and t test were used to verify, respectively, if there are difference between environmental data and G. schubarti abundance, between the two study areas. Linear regression was used to test the influence of litter cover and thickness over abundance. The environmental data differ (p=0.0208) between the areas, however, the abundance didn’t differ (p=0.8755), wasn’t influence of litter thickness and cover over abundance (p>0.05). This study suggests that G. schubarti is generalist and dominant competitive in the two areas.